Titanium-aluminum intermetallic compound reinforced copper-based composite material and preparation method and application thereof
By using titanium-aluminum intermetallic compound particles in copper-based composite materials and controlling the sintering conditions, the copper-titanium-aluminum alloy interface layer is solved, and the problem of insufficient hardness and wear resistance of the copper-based composite materials is achieved, and the high density of the material is achieved. Improved mechanical properties, simplifying process and reducing costs.
Patent Information
- Application Number
- CN202411420016.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
The existing copper-based composite materials have limited improvements in hardness and wear resistance, and the interface bonding between ceramic particles and copper substrate is complex, which increases process complexity and cost and makes it difficult to produce in industrialized production.
By using titanium-aluminum intermetallic compound (Ti-Al) particles as the reinforced phase, the sintering temperature and pressure are controlled to form a stable copper-titanium-aluminum alloy interface layer, and the hardness and wear resistance of the copper-based composite material are improved.
It has achieved the improvement of high density, mechanical properties and wear resistance of copper-based composite materials, simplified the preparation process, reduced costs, and is suitable for industrial mass production.
Smart Images

Figure CN119287209A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of metal-based composite materials, and in particular to a titanium-aluminum intermetallic compound reinforced copper-based composite material and a preparation method and application thereof. Background Art
[0002] Copper has high electrical and thermal conductivity and excellent processability, and is widely used in rail transit brake systems, wind power motor systems, etc. However, copper has low intrinsic strength, and its hardness and wear resistance are extremely limited. Currently, researchers mostly use ceramic particles to enhance the hardness and wear resistance of copper-based composites. Although the prepared copper-based composites have a good improvement effect on strength and wear resistance, the wettability between ceramic particles and the copper matrix is limited, and it is often necessary to chemically plate metal Cu, Ni, etc. on the surface of ceramic particles to improve interface bonding, which adds a more complex and cumbersome process to the process, and also increases great pressure on waste liquid treatment. In addition, the wear resistance of the prepared copper-based composites is limited.
[0003] For example, patent CN117070821B discloses a WC-Co metal ceramic particle gradient enhanced copper-based wear-resistant coating and a preparation method thereof, wherein a spraying powder in which the content of WC-17Co metal ceramic particles is gradiently increased in a CuSn10 alloy powder is sprayed layer by layer on the surface of a stainless steel substrate using a low-pressure cold spraying technique, thereby obtaining a copper-based wear-resistant coating material in which the metal ceramic WC-17Co particles have a gradient enhanced structure from the bottom layer to the surface in the coating. This preparation method is not only complicated to operate, but the use of rare metals also greatly increases the cost, which is not conducive to industrial production.
[0004] Based on this, there is an urgent need for a copper-based composite material with excellent wear resistance that has a simple preparation process and can be prepared at low cost to promote its application in the field of friction. Summary of the invention
[0005] To solve the above problems, the present invention provides a titanium-aluminum intermetallic compound reinforced copper-based composite material and a preparation method and application thereof, wherein titanium-aluminum intermetallic compound (Ti-Al) particles are used as a reinforcing phase, and the interfacial reaction relationship between the Ti-Al particles and the Cu matrix is controlled by controlling the sintering temperature and pressure, thereby forming a stable copper-titanium-aluminum alloy layer between the Ti-Al particles and the Cu matrix, which can not only effectively solve the interface problem between the reinforcing phase and the matrix, but also enable the prepared copper-based composite material to have an extremely high density while greatly improving the hardness, mechanical properties and wear resistance of the composite material.
[0006] Specifically, the following technical solutions are provided:
[0007] A first aspect of the present invention provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, comprising a copper matrix, titanium-aluminum intermetallic compound particles dispersed in the copper matrix, and a copper-titanium-aluminum alloy interface layer located between the copper matrix and the titanium-aluminum intermetallic compound particles.
[0008] Furthermore, the copper-titanium-aluminum alloy is Cu2TiAl.
[0009] Furthermore, the titanium-aluminum intermetallic compound includes a Ti3Al phase and a TiAl phase.
[0010] Furthermore, the mass percentage of the titanium-aluminum intermetallic compound in the titanium-aluminum intermetallic compound reinforced copper-based composite material is preferably 2%-4%, for example, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, etc., including but not limited to the mass percentages listed above.
[0011] Furthermore, the particle size of the titanium-aluminum intermetallic compound particles is 15-65μm, for example, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, etc., including but not limited to the particle sizes listed above; the layer thickness of the copper-titanium-aluminum alloy interface layer is 5-10μm, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc., including but not limited to the layer thickness listed above.
[0012] Furthermore, the average friction coefficient of the titanium-aluminum intermetallic compound reinforced copper-based composite material is less than 0.62.
[0013] The second aspect of the present invention provides a method for preparing the titanium-aluminum intermetallic compound reinforced copper-based composite material according to the first aspect, comprising the following steps: in a protective atmosphere,
[0014] (1) ball-milling titanium-aluminum intermetallic compound powder and copper powder to obtain a pre-sintered powder;
[0015] (2) placing the pre-sintered powder prepared in step (1) in a mold for cold pressing to obtain a green body;
[0016] (3) subjecting the green body prepared in step (2) to rapid hot pressing and sintering treatment to obtain the titanium-aluminum intermetallic compound reinforced copper-based composite material.
[0017] Furthermore, the protective atmosphere is preferably argon and / or nitrogen, and other inert gases may also be used.
[0018] Furthermore, in step (1), the titanium-aluminum intermetallic compound powder is preferably spherical or nearly spherical particles.
[0019] Furthermore, in step (1), the average particle size of the titanium-aluminum intermetallic compound powder is preferably 15-53 μm.
[0020] Furthermore, in step (1), the average particle size of the copper powder is preferably 5-20 μm.
[0021] Furthermore, in step (1), the mass ratio of the titanium aluminum intermetallic compound powder to the pre-sintered powder is (0.02-0.04):1, such as 0.02:1, 0.025:1, 0.03:1, 0.04:1, etc., including but not limited to the mass ratios listed above.
[0022] Furthermore, in step (1), in the step of ball milling and mixing, the ball-to-material ratio is preferably (5-10):1, the ball milling speed is preferably 200-400 rpm, and the ball milling time is preferably 4-8 h; in some preferred embodiments, the powder after ball milling and mixing is subjected to vacuum drying to obtain the pre-sintered powder; in the vacuum drying step, the vacuum degree is 2.0×10 -2 -1.0×10 -2 pa, temperature is 50-80℃, and drying time is 2-6h.
[0023] Furthermore, in step (2), the mold comprises a graphite mold.
[0024] Furthermore, in step (2), in the cold press forming step: the pressure is preferably 50 MPa-80 MPa, and the holding time is preferably 2-6 h.
[0025] Furthermore, in step (3), the rapid hot pressing sintering treatment is specifically as follows: placing the mold containing the green body in the cavity of the sintering furnace, evacuating the cavity and maintaining the hydraulic pressure at 30 MPa-50 MPa, and then heating the cavity to 780-820°C for 5-10 min, maintaining the pressure and cooling the cavity to below 60°C to obtain the titanium-aluminum intermetallic compound reinforced copper-based composite material.
[0026] Preferably, the vacuum degree of the sintering furnace cavity after evacuation is 1.0×10 -2 -1.0×10 -1 Pa.
[0027] In some preferred embodiments, the temperature rise treatment is specifically as follows: turning on the DC power supply, controlling the current to be between 1000A and 4000A, the voltage to be between 2V and 6V, and performing the temperature rise treatment at a temperature rise rate of between 80°C and 150°C / min.
[0028] The third aspect of the present invention provides an application of the titanium-aluminum intermetallic compound reinforced copper-based composite material described in the first aspect or the titanium-aluminum intermetallic compound reinforced copper-based composite material prepared by the preparation method described in the second aspect in the field of friction.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, which uses Ti-Al particles as a reinforcing phase, and generates a reaction layer (copper-titanium-aluminum alloy interface layer) by diffusion between the Ti-Al particles and a Cu matrix. The reaction layer becomes a link between the hard particles Ti-Al and the soft Cu matrix, and effectively solves the interface problem between the reinforcing phase and the Cu matrix. The prepared copper-based composite material has an extremely high density, and at the same time, the hardness, mechanical properties and wear resistance of the composite material are greatly improved, and the average friction coefficient is less than 0.62, and the composite material has good application prospects in the field of friction.
[0031] The present invention also provides a method for preparing the above-mentioned titanium-aluminum intermetallic compound reinforced copper-based composite material, which can be prepared by simple ball milling, cold pressing, and rapid hot pressing and sintering. The preparation process is simple, easy to operate and low in cost. In addition, a controllable interface reaction layer can be obtained by controlling the reaction temperature, which can not only ensure the interface performance of the Ti-Al particles and the Cu matrix, but also ensure that the high strength of the Ti-Al particles is retained inside the particles. The process has strong controllability, is suitable for industrial mass production, and is conducive to practical applications in the field of friction. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 SEM morphology of raw material Cu powder (a) and Ti-Al particles (b);
[0033] Figure 2 This is a SEM morphology image of the Ti-Al / Cu composite material prepared in Example 1;
[0034] Figure 3 is the selected area electron diffraction spot of the Ti-Al / Cu composite material reaction product in Example 1;
[0035] Figure 4 This is a SEM morphology image of the Ti-Al / Cu composite material prepared in Comparative Example 1;
[0036] Figure 5 This is the SEM morphology of the Ti-Al / Cu composite material prepared in Comparative Example 2;
[0037] Figure 6 The SEM morphology images of the raw material Cu powder (a) and the prepared Ti-Al / Cu composite material (b) used in Comparative Example 3;
[0038] Figure 7 This is the SEM morphology of the Ti-Al / Cu composite material prepared in Comparative Example 5. DETAILED DESCRIPTION
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0040] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0041] Example 1
[0042] This embodiment provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, and the preparation process thereof is as follows:
[0043] (1) In a vacuum glove box, the glove box was filled with an inert gas - high-purity argon. A precision electronic balance was used to weigh 0.60 g of Ti-Al powder (accounting for 2.0%) and 29.40 g of Cu powder into a vacuum ball mill. Stainless steel balls were placed in a vacuum milling jar. The ball-to-material ratio was 10:1, and the mass ratio of 10 mm diameter to 6 mm diameter was 1:1. The ball milling time was 5 h, and the rotation speed of the planetary ball mill was 300 r / min. After the ball milling, the mixed powder was placed in an environment at 50 °C for 4 h. The vacuum degree of the drying oven was 1.0 × 10 -2 pa. After vacuum drying, the pre-sintered powder can be obtained.
[0044] (2) Place the prepared pre-sintered powder and graphite mold together in a glove box and introduce high-purity argon gas to protect the powder from contact with moisture in the air to prevent oxidation and moisture. First, load the powder into the graphite mold and press the powder with graphite pressure heads at both ends. Since the graphite mold can only withstand limited pressure, the cold pressing pressure is controlled to 50 MPa. After maintaining the pressure for 5 hours, take out the mold containing the pre-sintered powder.
[0045] (3) Place the cold pressed mold in a rapid hot pressing sintering furnace, start the hydraulic system first, keep the pressure at 0.5t, then start the equipment to evacuate. When the vacuum reaches 1.0×10 -2Pa, the pressure began to increase, and the pressure was maintained at 50MPa. At this time, the DC power supply was turned on, and the current and voltage were controlled by the program, and the heating rate was maintained at 100℃ / min. After the temperature was raised to 800℃, the temperature and pressure were maintained for 10min. After the insulation was completed, the DC power supply was turned off, and the pressure was maintained until the mold was cooled to 60℃ and the sample was taken out. The Ti-Al / Cu composite material was obtained.
[0046] Figure 1 (a) is the SEM image of Cu powder, and (b) is the SEM image of Ti-Al particles. It can be seen from the figures that the morphology of the raw copper powder is mainly granular and dendritic, and the Ti-Al particles are spherical with good sphericity.
[0047] Figure 2 The metallographic SEM image of the Ti-Al / Cu composite material prepared in this embodiment shows that the Ti-Al and Cu matrix have a clear boundary line and a very uniform core-shell structure is obtained. It can be seen from the figure that the composition of the central dark area is determined to be Ti-Al particles, and the composition of the outermost light area is determined to be Cu. The selected area electron diffraction spot analysis of the middle core-shell reaction area is performed by TEM morphology, as shown in FIG. Figure 3 As shown, it is determined to be a Cu2TiAl compound. It is precisely because of the existence of this reaction product that the foundation is laid for improving the mechanical properties and wear resistance of the composite material.
[0048] Example 2
[0049] This embodiment provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, which differs from Embodiment 1 only in: the mass ratio of Ti-Al powder, ball milling parameters and sintering temperature, which are specifically as follows:
[0050] (1) In a vacuum glove box, the glove box was filled with an inert gas - high-purity argon. A precision electronic balance was used to weigh 1.20 g of Ti-Al powder (accounting for 4%) and 28.80 g of Cu powder in a vacuum ball mill. Stainless steel balls were placed in a vacuum milling jar. The ball-to-material ratio was 10:1, and the mass ratio of 10 mm diameter to 6 mm diameter was 1:1. The ball milling time was 5 h, and the rotation speed of the planetary ball mill was 400 r / min. After the ball milling, the mixed powder was placed in an environment at 50 °C for 4 h. The vacuum degree of the drying oven was 1.0 × 10 -2 pa. After vacuum drying, the pre-sintered powder can be obtained.
[0051] (2) Place the prepared pre-sintered powder and graphite mold together in a glove box and introduce high-purity argon gas to protect the powder from contact with moisture in the air to prevent oxidation and moisture. First, load the powder into the graphite mold and press the powder with graphite pressure heads at both ends. Since the graphite mold can only withstand limited pressure, the cold pressing pressure is controlled to 50 MPa. After maintaining the pressure for 5 hours, take out the mold containing the pre-sintered powder.
[0052] (3) Place the cold pressed mold in a rapid hot pressing sintering furnace, start the hydraulic system first, keep the pressure at 0.5t, then start the equipment to evacuate. When the vacuum reaches 1.0×10 -2 Pa, the pressure began to increase, and the pressure was maintained at 50MPa. At this time, the DC power supply was turned on, and the current and voltage were controlled by the program, and the heating rate was maintained at 100℃ / min. After the temperature was raised to 820℃, the temperature and pressure were maintained for 10min. After the insulation was completed, the DC power supply was turned off, and the pressure was maintained until the mold was cooled to 60℃ and the sample was taken out. The Ti-Al / Cu composite material was obtained.
[0053] Example 3
[0054] This embodiment provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, which differs from Embodiment 1 only in the mass ratio of Ti-Al powder and the sintering temperature, which are as follows:
[0055] (1) In a vacuum glove box, the glove box was filled with an inert gas - high-purity argon. A precision electronic balance was used to weigh 0.9 g of Ti-Al powder (3%) and 29.1 g of Cu powder in a vacuum ball mill. Stainless steel balls were placed in the ball mill. The ball-to-material ratio was 10:1, and the mass ratio of 10 mm diameter to 6 mm diameter was 1:1. The ball milling time was 5 h, and the rotation speed of the planetary ball mill was 300 r / min. After the ball milling, the mixed powder was placed in an environment at 50 °C for 4 h for drying. The vacuum degree of the drying oven was 1.0 × 10 -2 pa. After vacuum drying, the pre-sintered powder can be obtained.
[0056] (2) Place the prepared pre-sintered powder and graphite mold together in a glove box and introduce high-purity argon gas to protect the powder from contact with moisture in the air to prevent oxidation and moisture. First, load the powder into the graphite mold and press the powder with graphite pressure heads at both ends. Since the graphite mold can only withstand limited pressure, the cold pressing pressure is controlled to 50 MPa. After maintaining the pressure for 5 hours, take out the mold containing the pre-sintered powder.
[0057] (3) Place the cold pressed mold in a rapid hot pressing sintering furnace, start the hydraulic system first, keep the pressure at 0.5t, then start the equipment to evacuate. When the vacuum reaches 1.0×10 -2Pa, the pressure began to increase, and the pressure was maintained at 50MPa. At this time, the DC power supply was turned on, and the current and voltage were controlled by the program, and the heating rate was maintained at 100℃ / min. After the temperature was raised to 780℃, the temperature and pressure were maintained for 10min. After the insulation was completed, the DC power supply was turned off, and the pressure was maintained until the mold was cooled to 60℃ and the sample was taken out. The Ti-Al / Cu composite material was obtained.
[0058] Example 4
[0059] This embodiment provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, which differs from Embodiment 1 only in the mass ratio of Ti-Al powder and the sintering temperature, which are as follows:
[0060] (1) In a vacuum glove box, the glove box was filled with an inert gas, high-purity argon. A precision electronic balance was used to weigh 1.2 g of Ti-Al powder (accounting for 4%) and 28.8 g of Cu powder into a vacuum ball mill. Stainless steel balls were placed in a vacuum milling jar. The ball-to-material ratio was 10:1, and the mass ratio of 10 mm diameter to 6 mm diameter was 1:1. The ball milling time was 5 h, and the rotation speed of the planetary ball mill was 300 r / min. After the ball milling, the mixed powder was placed in an environment at 50 °C for 4 h for drying. The vacuum degree of the drying oven was 1.0 × 10 -2 pa. After vacuum drying, the pre-sintered powder can be obtained.
[0061] (2) Place the prepared pre-sintered powder and graphite mold together in a glove box and introduce high-purity argon gas to protect the powder from contact with moisture in the air to prevent oxidation and moisture. First, load the powder into the graphite mold and press the powder with graphite pressure heads at both ends. Since the graphite mold can only withstand limited pressure, the cold pressing pressure is controlled to 50 MPa. After maintaining the pressure for 5 hours, take out the mold containing the pre-sintered powder.
[0062] (3) Place the cold pressed mold in a rapid hot pressing sintering furnace, start the hydraulic system first, keep the pressure at 0.5t, then start the equipment to evacuate. When the vacuum reaches 1.0×10 -2 Pa, the pressure began to increase, and the pressure was maintained at 50MPa. At this time, the DC power supply was turned on, and the current and voltage were controlled by the program, and the heating rate was maintained at 100℃ / min. After the temperature was raised to 800℃, the temperature and pressure were maintained for 10min. After the insulation was completed, the DC power supply was turned off, and the pressure was maintained until the mold was cooled to 60℃ and the sample was taken out. The Ti-Al / Cu composite material was obtained.
[0063] Comparative Example 1
[0064] This comparative example provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, which is different from Example 1 only in that the sintering temperature is lowered to 700° C., and the other operations are the same to prepare the corresponding Ti-Al / Cu composite material.
[0065] Figure 4 This is the metallographic SEM morphology of the Ti-Al / Cu composite material prepared in Comparative Example 1. It can be seen from the figure that when the preparation temperature is reduced to 700°C, there is basically no diffusion reaction at the interface between the Ti-Al particles and the Cu matrix, which is only a simple mechanical bond, and no metallurgical bonding occurs, and no reaction layer appears. The pores around the particles are more distributed, and there are defects in the Cu matrix, which is not dense.
[0066] Comparative Example 2
[0067] This comparative example provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, which is different from Example 1 only in that the sintering temperature is increased to 900° C., and the other operations are the same to prepare the corresponding Ti-Al / Cu composite material.
[0068] Figure 5 The SEM metallographic morphology of the Ti-Al / Cu composite material obtained by sintering at a temperature of 900°C prepared in this comparative example. It can be seen from the figure that when the sintering temperature is increased to 900°C, the Ti-Al particles no longer have a spherical shape in the Cu matrix, and they diffuse excessively, leaving only some residual Ti-Al particles. As a result, the overall porosity increases, the density decreases, and the wear amount increases.
[0069] Comparative Example 3
[0070] This comparative example provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, which is different from Example 1 only in that irregularly shaped Ti-Al particles are used as the reinforcement phase, and the other operations are the same to prepare the corresponding Ti-Al / Cu composite material.
[0071] Figure 6 The SEM metallographic morphology of the Ti-Al / Cu composite material prepared by using irregular Ti-Al particles in this comparative example shows that the Ti-Al particles have a size of 15-53 μm and an irregular shape. Figure 6 As shown in (a), Figure 6 (b) is the metallographic SEM image of the Ti-Al / Cu composite material. When the same conditions are controlled and only the morphology of the Ti-Al particles is different, the Ti-Al particles are irregularly distributed and the particles diffuse in a disordered manner, which interrupts the continuity of the Cu matrix and makes it difficult to ensure the interface bonding performance between the Ti-Al particles and Cu in the composite material.
[0072] Comparative Example 4
[0073] This comparative example provides a pure Cu material, which is different from Example 1 only in that Ti—Al powder is not used as a reinforcement phase, and the other operations are the same to obtain a copper material.
[0074] Comparative Example 5
[0075] This comparative example provides a titanium-aluminum intermetallic compound reinforced copper-based composite material, which is different from Example 1 only in that the mass proportion of Ti-Al powder is 6.0%, and the other operations are the same to prepare the corresponding Ti-Al / Cu composite material.
[0076] Figure 7 This is the SEM metallographic morphology of the Ti-Al / Cu composite material prepared by using a higher content of Ti-Al particles in this comparative example. It can be seen from the figure that there are particle aggregation areas on the surface, which will lead to incomplete diffusion and bonding defects between particles, thereby affecting the performance of the composite material.
[0077] Performance Testing
[0078] The titanium-aluminum intermetallic compound reinforced copper-based composite materials or copper materials prepared in the above embodiments and comparative examples were tested for density, microhardness, ultimate tensile strength, average friction coefficient and wear rate, wherein:
[0079] Density: It is the ratio of actual density to theoretical density, used to characterize the density of materials;
[0080] Microhardness test: Shanghai Hengyi EM500-1A microhardness tester was used, with a loading force of 100 gf and a holding time of 15 s;
[0081] Ultimate tensile strength test: using Instron 34FM-100 electronic universal material testing machine, the tensile speed is 0.1mm / min;
[0082] Average friction coefficient test: measured using Rtec-MFT-5000-H multifunctional friction and wear testing machine, with an applied load of 50N, a reciprocating friction speed of 0.05m / s, and a grinding material of GCr15;
[0083] Wear volume test: The wear volume was measured by ZEISS LSM-700 laser confocal microscope, and then the wear volume was calculated.
[0084] The test results are summarized in Table 1
[0085] Table 1
[0086]
[0087] As shown in Table 1, compared with the pure copper material prepared in Comparative Example 4, the density of the Ti-Al / Cu composite material prepared in Examples 1-4 is improved, and the mechanical properties and wear resistance are significantly improved. This is because Ti-Al can diffuse with the Cu matrix to form a reaction layer, which becomes a link between the hard particles Ti-Al and the soft Cu matrix, thereby greatly improving the mechanical properties of the material; in addition, due to the high strength of the particles themselves, they act as a skeleton in the composite material, so during the friction and wear process, they support the grinding material and reduce the wear of the material.
[0088] It can be seen from Example 1 and Comparative Examples 1-2 that the sintering temperature has a great influence on the density, mechanical properties and friction properties of the composite material. Compared with the difficulty in forming a diffusion layer at a lower temperature (Comparative Example 1), the Ti-Al particles are difficult to retain at a higher temperature (Comparative Example 2). The composite material (Example 1) sintered at a suitable sintering temperature has a smaller density, microhardness, ultimate tensile strength, friction coefficient and wear amount, which can effectively improve the comprehensive performance of the composite material.
[0089] It can be seen from Example 1 and Comparative Example 3 that the morphology of Ti-Al particles has a great influence on the density and wear resistance of the composite material. Compared with irregularly distributed Ti-Al particles, using spherical Ti-Al particles as a reinforcing phase can greatly improve the density, mechanical properties and wear resistance of the composite material.
[0090] It can be seen from Example 1 and Comparative Examples 4 and 5 that the content of Ti-Al particles as the reinforcement phase should not be too much or too little. If the content of the reinforcement phase is too much, aggregation is likely to occur, which in turn is likely to cause bonding defects and reduce the density, mechanical properties and wear resistance of the composite material.
[0091] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A titanium-aluminum intermetallic compound reinforced copper-based composite material, characterized in that: The invention comprises a copper matrix, titanium-aluminum intermetallic compound particles dispersed in the copper matrix, and a copper-titanium-aluminum alloy interface layer located between the copper matrix and the titanium-aluminum intermetallic compound particles.
2. The titanium-aluminum intermetallic compound reinforced copper-based composite material according to claim 1, characterized in that: The titanium-aluminum intermetallic compound includes a Ti3Al phase and a TiAl phase; and the copper-titanium-aluminum alloy is Cu2TiAl.
3. The titanium-aluminum intermetallic compound reinforced copper-based composite material according to claim 1 or 2, characterized in that: The mass percentage of the titanium-aluminum intermetallic compound in the titanium-aluminum intermetallic compound reinforced copper-based composite material is 2%-4%.
4. The titanium-aluminum intermetallic compound reinforced copper-based composite material according to claim 1, characterized in that: The particle size of the titanium-aluminum intermetallic compound particles is 15-65 μm; the thickness of the copper-titanium-aluminum alloy interface layer is 5-10 μm.
5. A method for preparing the titanium-aluminum intermetallic compound reinforced copper-based composite material according to any one of claims 1 to 4, characterized in that: The process comprises the following steps: under a protective atmosphere, (1) ball-milling titanium-aluminum intermetallic compound powder and copper powder to obtain a pre-sintered powder; (2) placing the pre-sintered powder prepared in step (1) in a mold for cold pressing to obtain a green body; (3) subjecting the green body prepared in step (2) to rapid hot pressing and sintering treatment to obtain the titanium-aluminum intermetallic compound reinforced copper-based composite material.
6. The preparation method according to claim 5, characterized in that: In step (1), at least one of the following features is included: (1) The titanium-aluminum intermetallic compound powder is spherical or nearly spherical particles; (2) The average particle size of the titanium-aluminum intermetallic compound powder is 15-45 μm; (3) The average particle size of the copper powder is 5-20 μm; (4) The mass ratio of the titanium-aluminum intermetallic compound powder to the pre-sintered powder is (0.02-0.04):
1.
7. The preparation method according to claim 5, characterized in that: In step (1), in the ball milling mixing step, the ball-to-material ratio is (5-10):1, the ball milling speed is 200-400 rpm, and the ball milling time is 4-8 hours; Preferably, the powder after ball milling and mixing is vacuum dried to obtain the pre-sintered powder; in the vacuum drying step: the vacuum degree is 2.0×10 -2 -1.0×10 -2 pa, temperature is 50-80℃, and drying time is 2-6h.
8. The preparation method according to claim 5, characterized in that: In step (2), the mold comprises a graphite mold; In the cold pressing step, the pressure is 50 MPa-80 MPa and the holding time is 2-6 hours.
9. The preparation method according to claim 5, characterized in that: In step (3), the rapid hot pressing sintering treatment is specifically as follows: placing a mold containing the green body in a sintering furnace cavity, evacuating and maintaining a hydraulic pressure of 30 MPa-50 MPa, and then heating the temperature to 780-820°C for 5-10 minutes, maintaining the pressure and cooling the temperature to below 60°C to obtain the titanium-aluminum intermetallic compound reinforced copper-based composite material; Preferably, the vacuum degree of the sintering furnace cavity after evacuation is 1.0×10 -2 -1.0×10 -1 Pa; The temperature rise treatment is specifically as follows: turn on the DC power supply, control the current to be between 1000A and 4000A, the voltage to be between 2V and 6V, and perform the temperature rise treatment at a temperature rise rate of 80-150°C / min.
10. Use of the titanium-aluminum intermetallic compound reinforced copper-based composite material according to any one of claims 1 to 4 or the titanium-aluminum intermetallic compound reinforced copper-based composite material prepared by the preparation method according to any one of claims 5 to 9 in the field of friction.